PENGARUH IKLIM SEKOLAH DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DIMEDIASI MOTIVASI KERJA (Studi Kasus di SMK Swasta Se Kecamatan Tayu Kabupaten Pati) - Roro Widyah Prima Gumilang, 1052020130; Sutomo, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine and describe the effect of school climate and leadership to work motivation influence on the performance of teachers in private vocational high schools at District Tayu of Pati Regency. Sampling was done by census method so that all teachers in the private vocational high schools at District Tayu of Pati Regency totaling 66 persons used as a sample. Mechanical testing data used in this study include testing the validity of the factor analysis, reliability tests with Cronbach alpha formula, the multiple regression analysis, and tests of significance, the coefficient of determination to prove the truth of the hypothesis of research and testing mediation. The results showed that; 1) School climate has positive and significant effect on work motivation of teachers (0,000), 2) the school leadership has positive and significant effect on work motivation of teachers (0,000), 3) school climate has positive and significant effect on teacher performance (0.016), 4) school leadership has positive and significant effect on teacher performance (0.019), 5) Motivation has positive and significant effect on the performance of teachers (0,000), 6) Work motivation mediates the effect of school climate on the performance of teachers in private vocational high schools at District Tayu of Pati Regency, 7) Work motivation mediates the effect of school leadership on teacher performance in a private vocational high schools at District Tayu of Pati Regency. Keywords: school climate, school leadership, motivation, performance